MODELLING OF AN ACTIVATED SLUDGE WASTEWATER TREATMENT BIOPROCESS - ROMAN, Monica (Journal of Environmental Management and Tourism; Vol 1 No 2 (2010): JEMT Volume I Issue 2(2) Winter 2010, 2016)
This paper deals with the modelling of a biotechnological process used for wastewater treatment. Bond Graph method is an appropriate tool for modelling such a nonlinear process. The so-called pseudo Bond Graph method is proposed as a modelling technique for an aerobic process of biological wastewater treatment, the activated sludge bioprocess, which is carried out into a Continuous Stirred Tank Bioreactor. Also, the dynamical model of the two interconnected tanks operating bioprocess is presented. The obtained Bond Graph model and several simulations are conducted using 20sim modelling and simulation environment.